Comparative analysis of AQP7 expression and cryotolerance in X- and Y-chromosome bearing bovine sperm - Wang, Jieru; Li, Ruchun; Huang, Fei; Niu, Peng; Zheng, Yanling; Yuan, Dongfang; Du, Yan; Li, Congcong; Yang, Mingcai; Suo, Jiajia; Gao, Qinghua (Frontiers in Cell and Developmental Biology, 2025)
IntroductionThe livestock industry has witnessed a notable increase in the proportion of male calves born following artificial insemination with cryopreserved semen, hinting at a possible association between cryotolerance and inherent structural or functional disparities between X- and Y-chromosome bearing sperm. To delve into this phenomenon, we conducted a comprehensive proteomic analysis on bovine sex-sorted semen.MethodsSperm samples were meticulously categorized based on stringent quality parameters. Concurrent sorting of X- and Y-sperm from identical ejaculates was performed, followed by protein extraction for subsequent analysis. Quantitative isobaric tags for relative and absolute quantification (iTRAQ) were employed to identify differentially expressed proteins.ResultsiTRAQ pinpointed 20 proteins with differential expression between X- and Y-spermatozoa, including 12 upregulated and 8 downregulated proteins in Y-sperm. Aquaporin 7 (AQP7), significantly upregulated in Y-sperm, was identified as a key candidate. Western blot analysis corroborated elevated AQP7 expression in Y-sperm compared to X-sperm, while Aquaporin 3 (AQP3) showed no significant difference. Immunofluorescence revealed AQP7 localization to the post-acrosomal region, midpiece, and principal piece of Y-sperm with higher fluorescence intensity, whereas AQP3 distribution was comparable between groups.DiscussionThese findings imply a potential role for AQP7 in augmenting Y-sperm cryotolerance, providing molecular insights into sex-specific cryopreservation effects on fertility outcomes. Future research should elucidate AQP7’s functional mechanisms and explore implications for livestock breeding technologies.